1977
DOI: 10.1002/jso.2930090112
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of the arteries and veins of the breast

Abstract: Textbook accounts of this subject are inadequate. This review considers the work of Cooper and Salmon and reproduces some of their figures. Applications in the diagnosis and treatment of cancer are discussed. The largest mammary arteries are the lateral (from the axillary) and the anterior medial and posterior medial (from the internal thoracis). The branches of these arteries do not follow the duct system, but instead form a plexus in the anterior fat layer. Normally there are no hypervascular or hypovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…Breast vascularity may be affected by age, menstrual cycle, and vasoactive medications. 6 Studies of resistive index calculations across age groups have shown that premenopausal women generally have lower resistive indices than postmenopausal women, but with variability in resistive index calculations within the same breast as well as overlap between the 2 age groups. 7 On MRI, breast tissue and vascularity is often evident on both fat-sensitive (T1w) and fluid-sensitive (T2w) sequences.…”
Section: Normal Breast Vascular Anatomymentioning
confidence: 99%
“…Breast vascularity may be affected by age, menstrual cycle, and vasoactive medications. 6 Studies of resistive index calculations across age groups have shown that premenopausal women generally have lower resistive indices than postmenopausal women, but with variability in resistive index calculations within the same breast as well as overlap between the 2 age groups. 7 On MRI, breast tissue and vascularity is often evident on both fat-sensitive (T1w) and fluid-sensitive (T2w) sequences.…”
Section: Normal Breast Vascular Anatomymentioning
confidence: 99%
“…8 Additional studies on breast vasculature are included. 7,[10][11][12]15,16 These studies are interesting and include results commonly found today, along with multiple discrepancies, including currently unrecognized vessels.…”
Section: Venous Drainage Of the Breastmentioning
confidence: 89%
“…10 Salmon has observed the lateral mammary artery to arise from the external mammary artery, lateral thoracic artery, or directly from the axillary artery. 7 Occasionally, it is referred to as the lateral thoracic artery, which is thought to be incorrect as the lateral thoracic artery supplies the lateral upper chest wall.…”
Section: Lateral Mammary Arterymentioning
confidence: 98%
“…These vessels provide a route for metastatic emboli to the vertebral bodies, ribs, and central nervous system [15,16]. These venous communications are of particular significance in the breast, where the posterior intercostals arteries are in direct continuity with the vertebral plexus [17].Venous channels between this plexus and veins associated with thoracic, abdominal, and pelvic organs are present. These veins do not have valves, enabling flow in either direction.…”
Section: Discussionmentioning
confidence: 99%